The Significance of Deep Disagreements on Justice, Values, and Morals for Political Epistemology - Manuel Knoll (Public Reason)
Political epistemology asks whether there is knowledge about values, the good, the just, and the morally right that could be applied to political issues. Debates on such questions go back to the ancient Greeks. While Protagoras claims that no moral facts and no moral knowledge exist, both Socrates and Plato strive to overcome Protagoras’s skeptical claims. After reconstructing their debate, this article argues, in the tradition of Protagoras, that there is no ultimate moral knowledge to ethically orientate political decisions. The main argument against the existence of a mind-independent and objective moral reality about which moral knowledge could be achieved is based on the existence of myriad widespread deep disagreements on values, justice, morality, and ethics, which are resistant to rational solution. The arguments presented against ethical realism and cognitivism in section II are mainly based on Max Weber’s and Isaiah Berlin’s views that deep disagreements on values, morality, and ethics exist. The arguments set out against these positions in section III rest on deep philosophical disagreements on social and political justice, which are a characteristic feature of the history of political thought.